2017
DOI: 10.1093/biolre/iox152
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological blockage of the CXCR4-CXCL12 axis in endometriosis leads to contrasting effects in proliferation, migration, and invasion†

Abstract: High levels of inflammatory factors including chemokines have been reported in peritoneal fluid and blood of women with endometriosis. CXCL12 mediates its action by interaction with its specific receptor, CXCR4, reported to be elevated in human endometriosis lesions and in the rat model of endometriosis. Activation of the CXCR4-CXCL12 axis increases cell proliferation, migration, and invasion of cancer cells. To obtain insights into the CXCR4 expression profile in lesions and endometrium, as well as functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 41 publications
0
17
0
1
Order By: Relevance
“…CXCL12 interacts with its specific receptor, C-X-C motif chemokine receptor 4 (CXCR4), which is not consistently over-expressed in these three datasets though. The CXCL12-CXCR4 axis promotes proliferation, migration, and invasion of endometriotic cells 44,45 . In human papillary thyroid carcinoma, the CXCL12-CXCR4 axis promotes EMT processes by activating the NF-κB signaling pathway 46 .…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 interacts with its specific receptor, C-X-C motif chemokine receptor 4 (CXCR4), which is not consistently over-expressed in these three datasets though. The CXCL12-CXCR4 axis promotes proliferation, migration, and invasion of endometriotic cells 44,45 . In human papillary thyroid carcinoma, the CXCL12-CXCR4 axis promotes EMT processes by activating the NF-κB signaling pathway 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chemokines are key players in the activation and are recruitment of immune cells at sites of inflammation. The CXCR4/CXCL12 axis is functional in endometriosis and plays a role in a number of diverse cellular functions, including immune surveillance, inflammation response, tissue homeostasis, and tumor growth and metastasis (106). CXCR4 expression is upregulated by vascular endothelial growth factor (VEGF), and plays an important role in the malignant transformation of endometriosis (107).…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
“…Cell migration can be increased by the excessive expression of MMPs [37], leading to the local destruction of the extracellular matrix and the establishment of early lesions [38]. In fact, the levels of MMP-2 and MMP-9 were found to be higher in the peritoneal fluid of women with endometriosis compared to that of healthy patients [39,40]. Here, we have demonstrated that iron promotes the migration of human endometriotic cells and MMP-2 and MMP-9 expressions in human endometriotic cells.…”
Section: Discussionmentioning
confidence: 99%